Analisis Kepuasan Publik Terhadap Angkutan Umum Model Jak Lingko Sebagai Pengintegrasi Antar Moda Transportasi Publik Di DKI Jakarta - Wijianto, Wijianto; Istianto, Bambang; Rukman, Rukman (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
This study aims to analyze public satisfaction with public transportation in DKI Jakarta. As a metropolitan city as well as the capital city of the country, currently legally, it is no longer the capital of the country, but will be prepared as a global city. Jakarta residents who have reached more than 10 million people but in carrying out their mobility have not been supported by public transportation that satisfies its citizens. Although the destination of the trip has been facilitated by several modes of transportation such as MRT, commuter line and LRT which are rail and steel-based as well as Trans Jakarta and smaller land-based public transportation, it is not yet integrated. The policy of the DKI Jakarta Provincial government is to develop public transportation with a modern system called Jaklingko which functions as an intermodal integration. The operation of Jaklingko has been running for two years but has not been optimal and satisfies its users. This research method uses quantitative methods to measure how much public satisfaction with the Jaklingko. Jaklingko user satisfaction measurement is based on the theory of "service quality" from Parasuraman. The results of the study found that Jakarta residents who used Jaklingko stated that for the dimensions of the responsiveness and empathy variables the level of satisfaction reached above 80, meaning they were very satisfied with Jaklingko.